C-terminal tagging impairs AGO2 function - Kunal M. Shah; Alex F. F. Crozier; Anika Assaraf; Muzjda Arya; Paul Grevitt; Faraz Mardakheh; Michael J. Plevin; Tyson V. Sharp (RNA Biology, 2025)
MicroRNA-mediated gene silencing is a conserved mechanism of post-transcriptional gene regulation across metazoans. It depends on base pairing between small RNAs and mRNAs, and on protein complexes including the RNA-induced silencing complex (RISC), where Argonaute 2 (AGO2) plays a central role. A full understanding of RNA silencing requires reliable molecular tools to study AGO2 and RISC. Affinity tagging and antibody-based methods can introduce artefacts, and both the N- and C-terminal domains of AGO2 are critical for its function. While N-terminal tags are frequently used, and a recent study in mice showed altered activity in N-terminal HaloTag-AGO2 fusions, the consequences of C-terminal tagging remain underexplored. CRISPaint, a CRISPR-Cas9-based technique, enables endogenous C-terminal tag fusions without requiring homology arms. Using this system, we generated the first C-terminal HaloTag fusion of AGO2 (AGO2HALO) in human A549 cells. We found that the AGO2HALO fusion protein exhibits reduced binding with TNRC6A, with no effect on cell viability. However, it significantly impairs RNA cleavage, silencing activity, and nuclear localization. We further compared AGO2-EGFP and EGFP-AGO2 using transient transfection. N-terminally tagged AGO2 retained wild-type-like function and localization, while C-terminally tagged AGO2 was impaired in siRNA and miRNA silencing, nuclear import, and P-body localization. These results demonstrate that a C-terminal HaloTag compromises AGO2 functionality and is unsuitable for studying RISC biology. Our findings highlight the importance of validating tagging strategies to avoid misleading conclusions due to tag-induced functional defects. Pre-print, bioRxiv.